Pengaruh Diskon Flash Sale Dan Gratis Ongkos Kirim Terhadap Keputusan Customer Dalam Melakukan Pembelian Marketplace Shopee - Hendriyati Haryani; Chesa Salsabila; Nur Cahayati (UNIVERSITAS RAHARJA, 2023)
This study aims to explain the effect of flash sale discounts and free shipping on customer decisions in purchasing shopee marketplaces, especially for students of the Faculty of Economics and Business, Raharja University. The type of research used is quantitative research. The population in this study is the Shopee marketplace application users. This study used a population of 39 students for data collection by distributing questionnaires. While the data analysis technique used is multiple linear regression analysis technique. The results showed that the significance value of the results of the flash sale variable analysis (X1) on the purchasing decision variable (Y) in the Shopee marketplace had a positive effect, and the significance value of the results of the Free Shipping variable (X2) had a negative influence on the Purchase Decision variable (Y). on the Shopee marketplace. The results showed that flash sale and free shipping had a simultaneous effect on purchasing decisions